Nano-mechanical and tribological properties of a multilayered DLC coating under sub-ambient temperatures. (20th January 2011) - Chen, Jian; Bell, Gerard A.; Beake, Ben D.; Dong, Hanshan
The mechanical properties and tribological behaviour of a-C:H/TiCN/TiN coating were investigated at various sub-ambient temperatures for the first time using a newly developed low-temperature nanoindentation instrument. It has been found that the hardness and wear resistance of the a-C:H/TiCN/TiN coating increased with the decrease of the temperature.